Seroprevalence of Toxoplasma gondii in Wild Rats (Rattus rattus) in Northern Iran - Seyed Abdollah Hosseini; Saeid Abediankenari; Afsaneh Amouei; Shahabeddin Sarvi; Mehdi Sharif; Fatemeh Rezaei; Ahmad Daryani (Veterinary Medicine International)
Rodents are considered as reservoir hosts for various pathogens (such as Toxoplasma gondii) and have been revealed to play an important role in the spread of several infectious diseases to humans and other animals. The aim of this investigation was to survey the prevalence of anti-T. gondii IgG antibodies in wild rats in Northern Iran. One hundred rats were caught using rat traps set in different areas in Northern Iran (September 2017). The thoracic cavity of each rat was opened, and then the blood sample was collected from the heart. IgG anti-Toxoplasma gondii antibodies were detected using the modified agglutination test (MAT) with a cutoff value equal to 1 : 40. Overall, 56% of rats were infected by T. gondii. Considering the sex of rats, 45% of male and 55% of female rats were seropositive, but the differences were not statistically significant. There was a significant difference between seropositivity and habitat types and age of rodents. Our findings have public health implications and confirm the high seroprevalence of T. gondii infection in northern Iran. The study established that wild rats represent an important and persistent wildlife intermediate host reservoir for T. gondii.